Charge transfer mediated triplet excited state formation in donor–acceptor–donor BODIPY: Application for recording of holographic structures in photopolymerizable glass. Issue 32 (27th July 2022) - Mikulchyk, Tatsiana; Karuthedath, Safakath; De Castro, Catherine S. P.; Buglak, Andrey A.; Sheehan, Aimee; Wieder, Aaron; Laquai, Frédéric; Naydenova, Izabela; Filatov, Mikhail A.
Abstract : Novel BODIPY forming triplet excited states via the SOCT-ISC process was used for polymerization of methacrylate monomers inside a hybrid sol–gel material. Holographic recording of diffractive structures with high efficiency was demonstrated. Abstract : Donor–acceptor–donor BODIPY triads bearing anthracene or pyrene as electron donating subunits were prepared through a stepwise synthesis. Photoinduced electron transfer and formation of long-lived triplet excited states via spin–orbit charge transfer intersystem crossing (SOCT-ISC) was studied by steady-state and ultrafast pump-probe spectroscopy and further supported by DFT computations. New BODIPYs were found to form triplet states and sensitize singlet oxygen in both polar and non-polar solvents which is unusual for photosensitizers operating via SOCT-ISC. BODIPY-anthracene triad (ABA ) was used as a photosensitizer component in a photopolymerizable glass that was prepared by a four-step sol–gel process. ABA in combination with N -phenylglycin (NPG) showed the ability to initiate a free-radical polymerization of methacrylate monomers under 532 nm irradiation thus allowing for holographic recording of diffractive structures. High diffraction efficiency (up to 87%) obtained for ABA -NPG containing glass as compared to a reference diiodo-BODIPY (I2 BDP ) demonstrates for the first time that heavy-atom-free SOCT-ISC photosensitizers can efficiently operate in the solid state.